2010
DOI: 10.1017/s0022215110001520
|View full text |Cite
|
Sign up to set email alerts
|

Balloon sinuplasty: our first year

Abstract: We believe that balloon sinuplasty has a place in routine rhinology practice but that its applications are limited, and that its additional costs must be considered. We present advantages and possible limitations of the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Our results prove the safety and feasibility of this surgical procedure yet established in previous studies [13,21,22,23,24,25]. However we demonstrate the safety and efficacy of this technique also in onco-hematological patients with sinus dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…Our results prove the safety and feasibility of this surgical procedure yet established in previous studies [13,21,22,23,24,25]. However we demonstrate the safety and efficacy of this technique also in onco-hematological patients with sinus dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…Full‐length texts were then reviewed, and an additional 23 studies identified from references. A total of 31 studies were considered to be duplicates from the same cohort, and an additional 53 failed to meet inclusion/exclusion criteria. The final study list included 40 unique patient cohorts published from 2008 to 2016 and representing institutions from North America (n = 14), Europe (n = 12), Middle East (n = 6), Australia (n = 3), Asia (n = 3), and South America (n = 2) .…”
Section: Resultsmentioning
confidence: 99%
“…Hopkins et al . describing the results of balloon sinuplasty in 27 patients (67 sinuses) report no feasibility problems with successful dilatation achieved in 98% of sinuses . Raghunandhan et al .…”
Section: Discussionmentioning
confidence: 97%